2020
DOI: 10.1038/s41386-020-0656-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting inhibitory cerebellar circuitry to alleviate behavioral deficits in a mouse model for studying idiopathic autism

Abstract: Autism spectrum disorder (ASD) encompasses wide-ranging neuropsychiatric symptoms with unclear etiology. Although the cerebellum is a key region implicated in ASD, it remains elusive how the cerebellar circuitry is altered and whether the cerebellum can serve as a therapeutic target to rectify the phenotype of idiopathic ASD with polygenic abnormalities. Using a syndromic ASD model, e.g., Black and Tan BRachyury T + Itpr3 tf /J (BTBR) mice, we revealed that increased excitability of presynaptic interneurons (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 84 publications
(140 reference statements)
4
33
0
Order By: Relevance
“…We also found that BTBR mice display cognitive and emotional abnormalities akin to the psychiatric comorbidity of ASD [16,17]. In addition, similar neuroanatomical changes between the BTBR model and ASD subpopulations are reported [18,19].…”
Section: Introductionsupporting
confidence: 70%
“…We also found that BTBR mice display cognitive and emotional abnormalities akin to the psychiatric comorbidity of ASD [16,17]. In addition, similar neuroanatomical changes between the BTBR model and ASD subpopulations are reported [18,19].…”
Section: Introductionsupporting
confidence: 70%
“…The BTBR strain is a phenotypic model for idiopathic ASD, which exhibits impaired sociability, altered ultrasonic vocalization and increased self-grooming behaviors, simulating the main symptoms of human ASD [15]. We also found that BTBR mice display cognitive and emotional abnormalities akin to the psychiatric comorbidity of ASD [16,17]. In addition, similar neuroanatomical changes between the BTBR model and ASD subpopulations are reported [18,19].…”
Section: Introductionsupporting
confidence: 62%
“…Because of their respective deficit in social approaching or social novelty [16,33], in the three-chamber test, BTBR mice received DA before the habituation trial, whereas Fmr1-KO mice received DA before the sociability trial. As BTBR mice have intact recognition of social novelty [16,17], the social novelty trial was excluded here to avoid excessive administration of DA in the same subjects within a short time. The dosage and timing of DA administration were based on a previous study in mice [34] .…”
Section: Dopamine Administrationmentioning
confidence: 99%
See 2 more Smart Citations